THE EFFECT OF SELF-CONGRUITY AND BRAND CREDIBILITY ON PURCHASE DECISIONS WITH PURCHASE INTENTION AS A MEDIATING VARIABLE: : An Empirical Study on Apple MacBook Pro Products in Surabaya - Hondo, Immanuel Kurniawan (jfpublisher, 2024)
Purchasing decisions are individual activities directly involved in making decisions to make purchases of products offered by sellers. Purchase intention is an essential factor in the consumer decision-making process. In order for consumers to have interest in making purchases, strong branding is needed from the company. A strong brand can be obtained from the brand credibility that can be trusted, as well as information regarding the product position in a brand. Apart from a strong brand, companies nowadays also strive to create strong relational bonds with their consumers. This strong relational bond creates self-congruity as consumers decide to purchase and consume goods and services with an image that matches consumers' self-image. This research aims to examine the effect of brand credibility and self-congruity on purchase decisions for Apple MacBook Pro consumers in Surabaya through purchase intention as a mediating variable. This is a quantitative research with a survey method by distributing questionnaires to 150 respondents in Surabaya with a minimum age of 17 years, who were selected through purposive sampling technique. The data collected was analyzed with the Structural Equation Model (SEM). The findings of this research indicate that brand credibility and self-congruity directly influence the purchase intention of MacBook Pro users in Surabaya. Brand credibility and self-congruity were also found to directly influence purchase decision and indirectly through purchase intention of Apple MacBook Pro users in Surabaya.